1997
DOI: 10.1177/106002809703100608
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Pharmaceutical Care Services for Patients with Hyperlipidemias by Independent Community Pharmacy Practitioners

Abstract: Pharmaceutical care may positively affect lipid values, quality of life, and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…With little previous data available on expected changes in MAI the SF‐36 score was used to calculate the number of general practitioners required if each general practitioner enrolled 12 patients. Twelve patients were considered a manageable number of patients per pharmacist based the expected time requirements and on other studies [17–22] . The calculations were based on a clinically important change in SF‐36 score value being 10 units (physical function) and a standard deviation of 25 units, allowing for a clustering effect around the general practitioners with an intracluster correlation coefficient of 0.05, a level of significance of 0.05 and 80% power.…”
Section: Methodsmentioning
confidence: 99%
“…With little previous data available on expected changes in MAI the SF‐36 score was used to calculate the number of general practitioners required if each general practitioner enrolled 12 patients. Twelve patients were considered a manageable number of patients per pharmacist based the expected time requirements and on other studies [17–22] . The calculations were based on a clinically important change in SF‐36 score value being 10 units (physical function) and a standard deviation of 25 units, allowing for a clustering effect around the general practitioners with an intracluster correlation coefficient of 0.05, a level of significance of 0.05 and 80% power.…”
Section: Methodsmentioning
confidence: 99%
“…[46][47][48][49][50][51] The enhanced role of the pharmacist in preventive medicine has been advocated by the American Heart Association, 52 the British National Health Service, 53 a joint statement by the Canadian Medical Association and the Canadian Pharmacists' Association, 54 and others. 30,55,56 Pharmacists have successfully implemented preventive health programs in cholesterol management, [57][58][59][60][61] hypertension, 62 and other areas, 47,63 but often without comprehensive evaluation. Pharmacists may act as a link between the patient and the primary care physician, thus addressing many of the reported barriers to preventive care described by Hutchison et al 28 Project ImPACT was a nonrandomized observational study 61 of pharmacists' care of patients with hyperlipidemia carried out in 26 pharmacies that followed 397 patients for an average of 24.6 months.…”
Section: Commentmentioning
confidence: 99%
“…Pharmaceutical care has significantly reduced the occurrence of drug-related problems and fulfilled the desired outcomes of drug therapy in other diseases and conditions such as anticoagulation, hyperlipidemia, and asthma. [8][9][10][11][12][13] Studies have also shown that pharmacists' participation in the care of poorly controlled diabetic patients resulted in better outcomes. 14 However, pharmacists' participating in diabetic care are still not required to have CDE certification.…”
Section: Introductionmentioning
confidence: 99%